De-sacredizing of the Barong Dance Social Life in the Community Culture Bali - I Gusti Ngurah Sudiana (Institut Seni Indonesia Denpasar, 2010)
This article is the result of a research work in the village of Batubulan in 1998. In Batubulan there are two kinds of sacred barong which are given the title of Queen Gde Sakti and non-sacred Barong Tetamon for tourists’ performance. The two barong have the same shapes but have different functions. The sacred Barong (Ratu Gde Sakti) serves to drive out or neutralize all the diseases that are unseen, while the barong tetamon’s goal is to earn money. The sacred barong is housed at a place considered holy and sacred, being sacred on a particular day. While barong tetamon performs every day in the local stage without considering the good day, whether sacred or not. Tourists can watch the barong tetamon dance every day by paying the appropriate admission price that has been fixed by the owner of the stage. As a result of staging the many symbols and others, the sacred barong dance functions have changed their meaning when performed in the form of Barong Tetamon. De-sacralization processes have happened on various forms, e.g. the making, ceremonies, plays, the staging, staging time, and others. These changes are related to degrading the sacredness where there have been changes to the social meaning of barong dance. Due to changes in the meaning of it, it will slowly bring the cultural change of the society into a cultural market, particularly that of religion.